(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Today, in New Uzbekistan, freedom of conscience is fully guaranteed for all citizens by the world community. In the last decade, a number of positive achievements were made in the field of interreligious tolerance and interethnic harmony in our country. For instance, "Enlightenment and religious tolerance" resolution is equally recognized and practiced by all UN member states and it was initiated by Uzbekistan government, moreover the adoption of the resolution “Interreligious and intercultural dialogue and cooperation in the context of combating hate speech” also prepared by Uzbekistan and also 49 states, could be evidence of our opinion. This article contains priorities, problems, achievements and proposals for ensuring religious tolerance in the Republic of Uzbekistan.